AI personalization in marketing management: Consumer trust and purchase behavior in social commerce - El Shaddai Sandhy Pustap (International Journal of Economic and Business Research, 2026)
The rapid diffusion of artificial intelligence (AI) in social commerce platforms has fundamentally transformed how brands engage consumers through personalized marketing interventions. Despite growing scholarly interest in AI-driven personalization, the mediating role of consumer trust between AI personalization mechanisms and actual purchase behavior remains insufficiently examined, particularly within the social commerce context of developing economies. This study investigates the effects of AI personalization and perceived personalization on consumer trust and subsequent purchase behavior, with privacy concern as a moderating variable. A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed with data collected from 287 active social commerce users in Indonesia. Results reveal that AI personalization and perceived personalization positively and significantly influence consumer trust, which in turn mediates the relationship with purchase behavior. Privacy concern exerts a significant negative effect on consumer trust. These findings extend the Personalization-Privacy Paradox theory to the social commerce context and offer actionable implications for marketers deploying AI-based personalization systems.